1998
DOI: 10.1002/(sici)1097-0282(199803)45:3<231::aid-bip5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrophobic amino acids in gurmarin, a sweetness-suppressing polypeptide

Abstract: The sweetness‐suppressing polypeptide gurmarin isolated from Gymnema sylvestre consists of 35 amino acid residues and contains three intramolecular disulfide bonds. Nuclear magnetic resonance analysis showed that the hydrophobic side chains of Tyr‐13, Tyr‐14, Trp‐28, and Trp‐29 in gurmarin are oriented outwardly. Together with the hydrophobic side chains of Leu‐9, Ile‐11, and Pro‐12, they form a hydrophobic cluster, and therefore these hydrophobic groups are assumed to act as the site for interaction with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Gur-2 is more similar to Gur-1 (48.57% of identity and 65.71% of similarity in amino acid residues). Like Gur-1, Gur-2 has a hydrophobic and hydrophilic cluster on the surface of the molecule ( Ota et al 1998a ). Gur-2 is more hydrophobic than Gur-1 (Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gur-2 is more similar to Gur-1 (48.57% of identity and 65.71% of similarity in amino acid residues). Like Gur-1, Gur-2 has a hydrophobic and hydrophilic cluster on the surface of the molecule ( Ota et al 1998a ). Gur-2 is more hydrophobic than Gur-1 (Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acids of Gur-1 and Gur-2 involved in interactions with T1R2 and T1R3 are mainly Tyr13-Tyr14 and Trp28-Trp29 for Gur-1 and Phe14 and Trp28-Trp29 for Gur-2 (Supplementary Tables S3 – S6 ). Interestingly, hydrophobic amino acids Tyr14, Trp28, and Trp29 have been shown to be involved in the sweet-suppressing properties of Gur-1 ( Ota et al 1998a ; Sigoillot et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gur-2 is more similar to Gur-1 (48.57% of identity and 65.71% of similarity in amino acid residues). Like Gur-1, Gur-2 has a hydrophobic and hydrophilic cluster on the surface of the molecule (Ota et al, 1998a). Gur-2 is more hydrophobic than Gur-1 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acids of Gur-1 and Gur-2 involved in interactions with T1R2 and T1R3 are mainly Tyr13-Tyr14 and Trp28-Trp29 for Gur-1 and Phe14 and Trp28-Trp29 for Gur-2 (Tables S3-S6). Interestingly, hydrophobic amino acids Tyr14, Trp28 and Trp29 are showed involved in the sweet-suppressing properties of Gur-1 (Ota et al, 1998a; Sigoillot et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Other than these glycosides, conduritol-A with a tetrahydrox-yhexene structure has also been confi rmed to be involved in glucose absorption. Moreover, the peptide grumarin, consisting of thirty-fi ve amino acids, has been shown to be involved in suppression of sweetness (Ota et al, 1998). It has been reported that the saponins of ginseng showed a strong inhibitory effect on pancreatic lipase activity in vitro and suppressed the increase in body weight (Yun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%